Evaluation of the Management of Performing Arts Creation Learning - Sustiawati, Ni Luh; Negara, I Gede Oka Surya; Sumarno, Rano; Nalan, Arthur Supardan (Harmonia: Journal of Arts Research and Education, 2023)
The purpose of this study is to evaluate the learning management in the creation of performing arts at the Performing Arts Education Study Program at ISI Denpasar. The evaluation results of the learning management in the performing arts creation can be used as input for improving the learning management related to performing arts courses, which in turn can enhance students’ competence in the field of performing arts. The learning of performing arts creation is directed towards the development of nationalism among the next generation towards the cultural heritage of the nation in the field of arts. The research design used is an evaluative research design with the CIPP model. The research subjects consist of program managers, lecturers of the performing arts creation course, and students who have taken or are currently taking the performing arts creation course. Data collection is done using questionnaires, observations, and interviews. The data is analyzed using quantitative descriptive analysis. The research findings indicate that: (1) the quality of the Context Aspect of the learning management in the Performing Arts Education at ISI Denpasar is classified as good; (2) the quality of the Input Aspect of the learning management in the Performing Arts Education at ISI Denpasar is classified as fairly good; (3) the quality of the Process Aspect of the learning management in the Performing Arts Education at ISI Denpasar is classified as not good or poor; and (4) the quality of the Product Aspect of learning management in the Performing Arts Education at ISI Denpasar is classified as fairly good improved; (2) maximizing the use of technology in the learning process; (3) facilitating collaborative learning among students from different study programs or universities.